IMPLEMENTASI AKAD PEMBIAYAAN MURABAHAH - Ramadana, Sri Winarsih (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
Murabahah financing is one type used in the Islamic financial system. A murabahah contract is a sale and purchase contract at a price disclosed and acknowledged by both parties since the beginning of the transaction. In murabahah contract financing, the bank or financial institution as the financing party will buy the goods the customer needs and resell them to the customer at a price previously disclosed. The research aims to determine how the murabahah contract financing is implemented at the SRB. The research method used by the author in this study is descriptive analysis with a qualitative research approach. The study results show the implementation of murabahah financing at PT.BPRS HikmahWawaah starts with financing applications, collecting the necessary files, conducting surveys to check prospective customers, and PT.BPRS HikmahWawaah, in deciding whether to provide financing to prospective customers, must go through a meeting financing committee to see whether the prospective customer can pay off his obligations. In assessing the financing, BPRS Hikmah Wahyuah uses the 5 C principles: character, capacity, capital, collateral, and economic conditions.